2023
DOI: 10.1038/s41420-023-01450-w
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Notch4 promotes tumorigenesis and inhibits metastasis of triple-negative breast cancer via Nanog and Cdc42

Abstract: Elucidation of individual Notch protein biology in specific cancer is crucial to develop safe, effective, and tumor-selective Notch-targeting therapeutic reagents for clinical use [1]. Here, we explored the Notch4 function in triple-negative breast cancer (TNBC). We found that silencing Notch4 enhanced tumorigenic ability in TNBC cells via upregulating Nanog expression, a pluripotency factor of embryonic stem cells. Intriguingly, silencing Notch4 in TNBC cells suppressed metastasis via downregulating Cdc42 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…To evaluate the function of tumoral Notch4, we first determined tumor cell and stromal cell types that express Notch4. Prior studies have indicated that Notch4 can be expressed by tumor endothelium, immune cells, and some cancer cells ( 24 27 ). We examined the presence of Notch4 by IF staining of tumors derived from Calu-6 non–small cell lung carcinoma (NSCLC) and MDA-MB-231 triple-negative breast carcinoma implanted into BALB/c nude mice.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the function of tumoral Notch4, we first determined tumor cell and stromal cell types that express Notch4. Prior studies have indicated that Notch4 can be expressed by tumor endothelium, immune cells, and some cancer cells ( 24 27 ). We examined the presence of Notch4 by IF staining of tumors derived from Calu-6 non–small cell lung carcinoma (NSCLC) and MDA-MB-231 triple-negative breast carcinoma implanted into BALB/c nude mice.…”
Section: Resultsmentioning
confidence: 99%
“…Suppressing Notch 3 has been investigated to limit metastasis and enhance cell response to chemotherapy [ 60 , 61 ], as well as affect the tumour microenvironment and decrease activation of cancer-associated fibroblasts [ 62 ]. Notch 4’s role in breast cancer is not well-defined compared to other Notch receptors, but has been linked to angiogenesis and vascularization, which may influence tumour growth and metastasis [ 63 ]. Expression of Notch 4 is associated with the basal-like subtype of breast cancer.…”
Section: Introductionmentioning
confidence: 99%